2022
DOI: 10.1021/acs.energyfuels.2c01835
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Perspectives of Fiber-Shaped Batteries

Abstract: Intelligent electronics are drawing vast attention with an enormous market and revolutionizing the daily lives of humans in extensive fields. Fiber-shaped batteries (FSBs), which act as the core component of wearable electronics, demonstrate superior flexibility, wearability, mechanical stresses, adaptability to deformation, and scale production with a unique one-dimensional architecture. However, many difficulties, including a complicated fabrication process, high internal resistance, and poor stability, hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…The electrostatic spinning method is a technique developed in recent years for the preparation of electrolytes for high-performance cells. By this method, a laminar fibrous film with high porosity and small pore size can be obtained. , And, the electrostatic spinning method can be used not only for the preparation of SSEs but also for the preparation of wearable devices such as fiber-shaped batteries with superior flexibility and fiber-based electrochemical supercapacitors with high energy density. Recent studies have shown that electrostatic spinning can regulate the microscopic morphology of electrolyte membranes on the nanometer scale and obtain a fiber framework of a large specific surface area with uniform morphology. The pore configuration of the electrostatic spinning film can accelerate the migration of Li + , which makes it difficult for polymer molecular chains and inorganic salts to form crystalline regions. As a result, electrostatic spinning can be a more efficient CPE preparation process than solution casting.…”
Section: Increasing the Electrochemical Performance Of Pvdf-based Cpesmentioning
confidence: 99%
“…The electrostatic spinning method is a technique developed in recent years for the preparation of electrolytes for high-performance cells. By this method, a laminar fibrous film with high porosity and small pore size can be obtained. , And, the electrostatic spinning method can be used not only for the preparation of SSEs but also for the preparation of wearable devices such as fiber-shaped batteries with superior flexibility and fiber-based electrochemical supercapacitors with high energy density. Recent studies have shown that electrostatic spinning can regulate the microscopic morphology of electrolyte membranes on the nanometer scale and obtain a fiber framework of a large specific surface area with uniform morphology. The pore configuration of the electrostatic spinning film can accelerate the migration of Li + , which makes it difficult for polymer molecular chains and inorganic salts to form crystalline regions. As a result, electrostatic spinning can be a more efficient CPE preparation process than solution casting.…”
Section: Increasing the Electrochemical Performance Of Pvdf-based Cpesmentioning
confidence: 99%
“…In recent years, one dimensional energy storage devices made from fabric and spring designs are adapted as well due to their exceptional flexibility. [19][20][21][22][23] Considering the distinctive features of each structure listed above, it is crucial to investigate current state-of-the-art progress in novel structural designs, which includes selection criteria, geometrical parameters and various applications of these structures in energy storage. In particular, the geometrical parameters employed to create ultra-strong microstructures by tuning the length (c), joining angle (y) and arc radius (R) of each particular structure are elucidated.…”
Section: Woon Gie Chongmentioning
confidence: 99%
“…However, wearable power sources are constructed from flexible and mechanically stable components to meet utility demands. Typically, they consist of flexible electrode films attached to the surface of flexible current collectors, gel polymer electrolytes or thin porous membranes soaked with an electrolyte, and packaging materials. Moreover, they can be manufactured in a sandwich form, interdigitated, or in a fiber-like configuration. The integration of all constituents of flexible storage devices is provided by synthetic polymers. Unfortunately, besides good processability and durability, synthetic polymers have a negative environmental impact due to their non-biodegradable nature and fossil fuel origin.…”
Section: Flexible Energy Storage Devicesmentioning
confidence: 99%